Accessible adaptive optics and super-resolution microscopy to enable improved imaging - Hall, N (2020)
Many of the recent innovations in biological imaging have revolved around the quest for greater resolving power, ultimately culminating in the advent of super-resolution microscopy techniques. However, all microscopy techniques are vulnerable to optical aberrations which distort the light wavefront. This leads to a gulf between theoretical and practical resolution for an imaging system. For super-resolution techniques, this can lead to reconstruction artifacts or the failure of the imaging technique entirely.